Association between body mass index and cognitive impairment in Chinese older adults - Dong, Wenshuo; Kan, Lichao; Zhang, Xinyue; Li, Mengli; Wang, Meijuan; Cao, Yingjuan (Frontiers in Public Health, 2023)
Background The association between body mass index (BMI) and the risk of cognitive impairment remains uncertain. Relatively few studies have analyzed the dose–response relationship between BMI and cognitive impairment. This article utilized nationally representative longitudinal data to assess the association between BMI and cognitive impairment in Chinese older adults. Objective The present study aimed to analyze the association between BMI and cognitive impairment in Chinese older people, including an investigation of gender differences and the dose–response relationship. Methods Data were obtained from the China Health and Retirement Longitudinal Study database in 2015 and 2018. The present study used logistic regression to analyze the relationship between baseline BMI and cognitive impairment, and adopted a restricted cubic spline model to plot dose–response curves for baseline BMI and prevalence of risk of cognitive impairment. Results The mean BMI of the survey population was 23.48 ± 3.66 kg/m2, and the detection rate of cognitive impairment was 34.2%. Compared to the normal weight group (18.5 ≤ BMI < 23.9 kg/m2), the odds ratio (OR) for cognitive impairment was 1.473 (95% CI: 1.189–1.823) in the underweight group (BMI < 18.5 kg/m2), whereas the corresponding OR was 0.874 (95% CI: 0.776–0.985) for the overweight or obese group (BMI ≥ 24.0 kg/m2) after adjusting for confounders. Gender subgroup analysis showed that overweight or obese older women were less likely to develop cognitive impairment (OR = 0.843; 95% CI: 0.720–0.987). The results of the restricted cubic spline analysis revealed a curvilinear L-shaped relationship between BMI and the risk of cognitive impairment (P non-linearity <0.05). In particular, the risk of cognitive impairment was higher at a lower baseline BMI. In contrast, BMI in the range of 23.2–27.8 kg/m2 was associated with a decreased risk of cognitive impairment. Conclusion BMI is a dose-dependent related factor for cognitive impairment in Chinese older adults. Being underweight is a risk factor for the development of cognitive impairment, while being overweight or obese is less likely to have cognitive impairment, particularly in female older people. Keeping BMI ranging from 23.2–27.8 kg/m2 in older adults can help maintain cognitive function.